The unanswered Questions in Hyperuricemia: is it a cause of chronic kidney disease, a compensation mechanism, a coincidence, a consequence of disease or concurrent phenomenon? - M. Kolesnyk (Ukrainian Journal of Nephrology and Dialysis, 2018)
Chronic kidney disease (CKD) has become a global public health problem because of its high prevalence and the accompanying increase in the risk of end-stage renal disease, cardiovascular disease, and premature death. The role of uric acid (UA) in the pathogenesis and progression of CKD remains controversial. Although many evidence-based studies have suggested that UA itself may harm patients with CKD by increasing inflammation and CKD progression, the issue is still a matter of discussions. In this review we try to clarify what is hyperuricemia – cause of CKD, compensation, coincidence, consequence of CKD or it is only an epiphenomenon, and to evaluate current evidence of different types of targeted hypouricemic therapy effectiveness. So, to treat or not to treat?